PERTUMBUHAN DAN HASIL TANAMAN KACANG HIJAU (Vigna radiata L.) YANG DITANAM DI GAWANGAN MATI KELAPA SAWIT BEDA UMUR DAN PEMBERIAN PUPUK KANDANG SAPI DI LAHAN GAMBUT - Trisnawati, Ice; Murniati, Murniati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to determine the growth and better production of green bean plants (Vigna radiata L.) grown in oil palm inter row with different age and cow manure application on peatlands. Research has been conducted on peatlands Experimental Station, Faculty of Agriculture, University of Riau, Rimbo Panjang Village, Tambang District, Kampar, from August to October 2016. The study was conducted experimentally arranged in split plot design (Split Plot Design) by the planting of green beans in oil palm inter row with different ageconsists of: G1: In oil palm inter row with plant age of 2.5 years, G2: oil palm inter row aged 4 years and the subplot was the dose of cow manure consisting of: P1: 5 ton.ha-1, P2: 10 ton.ha-1, P3: 15 ton.ha-1, P4: 20 ton.ha-1, with the size of 180 cm x 150 cm. Parameters those measured were plant height, number of primary branches, flowering age, harvesting age, pithy number of pods per plant, seed weight per plot and weight of 100 seeds. Data were analyzed using ANOVA then tested further using DNMRT at the 5 % level.The cow manure on green bean plants grown oil palm inter row gave effect to the production of green bean plants, but not on growth.Green pea plants grown on oil palm inter row age of 2,5 years with cow manure 15 ton.ha-1 resulted in better production.  Keywords: Green bean, oil palm inter row with different age, cow manure